Resource integration for multiple benefits: Multifunctionality of integrated farming systems in Northeast Thailand - Prasnee Tipraqsa (2018)
Resource degradation in rice farming systems in Thailand endangers food security, but the systems may become more sustainable by combining them with aquaculture and livestock farm enterprises by capitalization of their synergies in resource use and re-use, i.e. by adopting integrated farming systems. Most empirical studies that assess this potential have focused on a few specific aspects, but not on the multiple social, economic, and ecological functions of resource integration. This study uses the framework of multifunction agriculture to assess the performance of integrated farming systems in Thailand and compares its performance with that of 'normal-rice' or non-integrated farming systems. Surveys were conducted in Khon Kaen province of Northeast Thailand using a combination of quantitative and qualitative survey methods. Integrated farming systems were found to outperform the normal or commercial farming systems in all four dimensions of a multifunctional agriculture: food security, environmental functions, economic functions, and social functions. The findings support the notion that diversification and integration of resources on farms is feasible in both economic and ecological terms. The analyses shows that integrated farming does not, however, diminish the need for external inputs. High start-up cost might constrain farmers from switching to integrated farming and from exploiting the benefits of resource integration. © 2007 Elsevier Ltd. All rights reserved.